Measurement of Thermal Conductivity of Foods in Situ by aNon-Steady State Method - Ali, Asbi; Tew, K. K. (Universiti Putra Malaysia Press, 1993)
An improved line heat source thermal conductivity probe was designed to simplify the construction and extend the life of thermal conductivity probes for use in the determination of thermal properties of foods. The probe was designed with the thermocouple on the outside of a cylindrical heater instead of being placed inside a hypodermic needle as used by most researchers in the literature. The utility of the apparatus was checked by measuring the thermal conductivity of food samples with varying conditions of moisture content and at different ambient temperatures. Linearity of temperature versus logarithm of time was obtained after 8 to 10 minutes (r2 = 0.985).